ANALYSIS OF TWO-WHEELED ONLINE TRANSPORTATION USAGE IN BANDAR LAMPUNG (Case Study: Maxim, GoJek, and inDrive) - Imam Buchori; Fery Hendi Jaya (PT. Radja Intercontinental Publishing, 2026)
Advancements in information and communication technology have driven the transformation of transportation systems toward app-based (online) services. The emergence of online two-wheeled transportation has provided urban residents with mobility alternatives that are easier, faster, more economical, and more flexible. In Bandar Lampung City, competition among online transportation providers—such as Gojek , Maxim, and InDrive —has intensified, necessitating an evaluation of user preferences and the quality of services provided. This study aims to analyze the usage of online two-wheeled transportation in Bandar Lampung City and compare user perceptions regarding the service performance of each application based on aspects such as cost-effectiveness, accessibility, comfort, safety, facilities, satisfaction, and supporting infrastructure. The study is grounded in Law Number 22 of 2009 concerning Traffic and Road Transportation and Ministry of Transportation Regulation Number 12 of 2019 concerning Safety Protection for Motorcycle Users in Public Transportation Services. A descriptive research method with a quantitative approach was employed, using questionnaires distributed to users of online two-wheeled transportation in Bandar Lampung City. The data were analyzed using descriptive statistics to outline respondent characteristics and preference levels for each service provider. The results indicate that 62% of respondents use Gojek , 15% use Maxim, 5% use InDrive , and 18% use other online transportation applications. Gojek's high usage rate is attributed to respondents' favorable assessments regarding cost-effectiveness, accessibility, and travel time; riding comfort and safety; facilities and user satisfaction; perceptions of supporting infrastructure; and perceptions regarding the service provider's sustainability. The findings reveal that service quality, ease of access, and user trust are the primary factors influencing public choice regarding online two-wheeled transportation services in Bandar Lampung City. These results are expected to provide valuable insights for local government and service providers to enhance the quality of online transportation services, ensuring they are safe, comfortable, efficient, and sustainable.